HLA‐DR polymorphism in SARS‐CoV‐2 infection and susceptibility to symptomatic COVID‐19. Issue 1 (8th March 2022) - Astbury, Stuart; Reynolds, Catherine J.; Butler, David K.; Muñoz‐Sandoval, Diana C.; Lin, Kai‐Min; Pieper, Franziska P.; Otter, Ashley; Kouraki, Afroditi; Cusin, Lola; Nightingale, Jessica; Vijay, Amrita; Craxford, Simon; et al.
Abstract: SARS‐CoV‐2 infection results in different outcomes ranging from asymptomatic infection to mild or severe disease and death. Reasons for this diversity of outcome include differences in challenge dose, age, gender, comorbidity and host genomic variation. Human leukocyte antigen (HLA) polymorphisms may influence immune response and disease outcome. We investigated the association of HLAII alleles with case definition symptomatic COVID‐19, virus‐specific antibody and T‐cell immunity. A total of 1364 UK healthcare workers (HCWs) were recruited during the first UK SARS‐CoV‐2 wave and analysed longitudinally, encompassing regular PCR screening for infection, symptom reporting, imputation of HLAII genotype and analysis for antibody and T‐cell responses to nucleoprotein (N) and spike (S). Of 272 (20%) HCW who seroconverted, the presence of HLA‐DRB1*13:02 was associated with a 6·7‐fold increased risk of case definition symptomatic COVID‐19. In terms of immune responsiveness, HLA‐DRB1*15:02 was associated with lower nucleocapsid T‐cell responses. There was no association between DRB1 alleles and anti‐spike antibody titres after two COVID vaccine doses. However, HLA DRB1*15:01 was associated with increased spike T‐cell responses following both first and second dose vaccination. Trial registration: NCT04318314 and ISRCTN15677965. Abstract : SARS‐CoV‐2 infection results in different outcomes ranging from asymptomatic infection, to mild or severe disease and death. We investigated the association of HLAII alleles with case definition symptomatic COVID‐19, virus‐specific antibody and T cell immunity. Presence of HLA‐DRB1*13:02 was associated with increased risk of symptomatic COVID‐19, while, after vaccination, HLA DRB1*15:01 was associated with increased spike T cell responses.